Reflectivity of the dense xenon plasma - Shalenov, E. O.; Dzhumagulova, K. N.; Ramazanov, T. S.; Röpke, G.; Reinholz, H. (21st International Symposium on Heavy Ion Inertial Fusion. Autonomous Organization of Education “Nazarbayev University”, 2016)
The investigation of optical properties of the dense xenon plasma is important for the realization of different technological applications [1-2]. In this work we consider the dense partially ionized xenon plasma consisting of the electrons, ions and atoms...
Keywords: xenon plasma; ions; atoms; Research Subject Categories::NATURAL SCIENCES::Physics::Elementary particle physics